Maintaining and Developing Ethical Corporate Culture - Moslem Soleymanpor (Journal of Global Pharma Technology, 2017)
Of all the issues boards of directors, executives, and managers face, one could argue that unethical corporate activity is one of the most signiﬁcant in terms of its potential negative impact and also one of the most difﬁcult to properly address. This article argues that three key elements must exist if illegal or unethical activity within and on behalf of organizations is to be minimized through developing and sustaining an ethical corporate culture. The three elements include (1) the existence of a set of core ethical values infused throughout the organization in its policies, processes, and practices; (2) the establishment of a formal ethics program, including a code of ethics, ethics training, an ethics hotline, and an ethics ofﬁcer; and (3) the continuous presence of ethical leadership-that is, an appropriate ‘tone at the top’ as reﬂected by the board of directors, senior executives, and managers. While each of these three elements is distinct, they also overlap, relate to, and reinforce each other. This article discusses each of the three key elements necessary to develop and maintain an ethical corporate culture. Keywords: Ethical corporate culture; Ethical values; Ethics programs; Ethical leadership.